PENINGKATAN PENGETAHUAN PERILAKU SEKSUAL BERESIKO DIKALANGAN SISWA SMP N 13 PELAYANGAN KOTA JAMBI - Rumita Ena Sari; Fitria Eka Putri; Sri Astuti Siregar (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2020)
Data from the Jambi City Health Office shows that 77 girls who were pregnant <18 years, 34girls who give birth <18 years, 10 people with gonorrhea, 9 people with STIs (Sexually Transmitted Infections) and 7 people with ISR (Infection Reproductive). Based on the Monthly Report on Disease Prevention and Control (P2P), the Jambi City Health Office, it was found that 14 people were HIV positive (15-24 years). This community service aims to increase knowledge about risky sexual behavior among students of SMP N 13 Pelayangan Jambi City. This activity was in partnership with SMP N 13 Pelayangan Jambi City. However, it was involved all schools, especially students, as targets for increasing knowledge. Activities was carried out from compiling an activity plan to monitoring and evaluating activities according to the specified targets and outputs. Furthermore, there has been an increase in students' knowledge about risk of sexual behavior from the results of the pre and post tests that have been done. Increasing knowledge about risky sexual behavior among students of SMP N 13 Pelayangan Jambi City has been carried out well. Increasing knowledge of students after pre-test and post-test, which initially only 40% knew after the socialization and delivery of material increased to 70%.